¿QUÉ ESPERAR CUANDO SE BRINDA LACTANCIA MATERNA POR PRIMERA VEZ? - Hernández Pena, Melanie Yahaira; Valenzuela Calvillo, Linda Selen; Arellano Ortiz, Ana Lidia; arellano, ana (2024)
https://www.ugto.mx/campusleon/dcs/images/redicinaysa/publicaciones/2024/REDICINAYSA-2024-Vol-17-No-5-Sep-Oct-2024.pdf